1998
DOI: 10.1152/ajpcell.1998.275.5.c1357
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide to PKC-ε alters cAMP-dependent stimulation of CFTR in Calu-3 cells

Abstract: Protein kinase C (PKC) regulates cystic fibrosis transmembrane conductance regulator (CFTR) channel activity but the PKC signaling mechanism is not yet known. The goal of these studies was to identify PKC isotype(s) required for control of CFTR function. CFTR activity was measured as36Cl efflux in a Chinese hamster ovary cell line stably expressing wild-type CFTR (CHO-wtCFTR) and in a Calu-3 cell line. Chelerythrine, a PKC inhibitor, delayed increased CFTR activity induced with phorbol 12-myristate 13-acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Finally, depletion of endogenous PKC␤ using an antisense approach partially in- hibited the induction process. Using this approach, various laboratories have earlier established a specific role for PKC isoforms in various cellular processes (40)(41)(42). Taken together, these results support involvement of a PKC␤-dependent pathway in the induction of LDL receptor transcription by p42/44 MAPK .…”
Section: Discussionsupporting
confidence: 61%
“…Finally, depletion of endogenous PKC␤ using an antisense approach partially in- hibited the induction process. Using this approach, various laboratories have earlier established a specific role for PKC isoforms in various cellular processes (40)(41)(42). Taken together, these results support involvement of a PKC␤-dependent pathway in the induction of LDL receptor transcription by p42/44 MAPK .…”
Section: Discussionsupporting
confidence: 61%
“…Although CFTR is regulated primarily by cAMP-dependent protein kinase A (PKA), it is stimulated to a modest extent by protein kinase C (PKC). In addition, our laboratory and others reported that inhibition of PKC activity using a general PKC inhibitor chelerythrine prevented forskolin-or epinephrinestimulated CFTR function (3)(4)(5). This laboratory established that activity of PKC⑀ is necessary for cAMP-dependent CFTR function.…”
mentioning
confidence: 75%
“…The Calu-3 cell line is a serous cell line, which we have shown expresses CFTR and secretes chloride in response to elevations in cAMP (4,27). CFTR activity is also modulated by an interaction with the Na ϩ /H ϩ exchange regulatory factor (NHERF1), a 50-kDa protein that is also known as EBP50 (ezrin-radixinmoesin-binding phosphoprotein-50).…”
mentioning
confidence: 97%
“…With specific inhibitors and siRNA treatments we found that only PKC, a novel calciumindependent isoform, mediated VIP-dependent increase in CFTR membrane stability in the JME/CF15 epithelial nasal cells and also in the recombinant BHK cells stably expressing wild-type or F508-CFTR (Alcolado et al, 2011). This is not surprising as PKC was previously reported to co-localize with CFTR at the apical membrane of airway epithelial cells and to play a permissive role on CFTR-dependent chloride secretion (Liedtke and Cole, 1998;Liedtke et al, 2001;Liedtke et al, 2002). The C-terminal of CFTR interacts with either CAL or NHERF1.…”
Section: Role Of Pkcmentioning
confidence: 51%